2008
DOI: 10.1051/0004-6361:200810619
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the near infrared identification of carbon stars

Abstract: Context. Thousands of C stars have been identified in Local Group galaxies using narrow band photometry. To survey C stars at larger distances and alternative to the narrow-band approach is needed. Aims. We obtain, from ESO Archive data, NIR magnitudes and colours of previously known C stars in two dwarf irregular Local Group galaxies, namely IC 1613 and NGC 3109. Methods. We compare the NIR magnitudes and colours of the C star populations, previously identified from narrow band techniques to estimate the star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…In their study of IC 1613, Battinelli & Demers (2009) conclude that a cut at (J − K s ) = 1.40 mag would provide a reliable sample of C-type stars. From Fig.…”
Section: Colour Selection 331 C-and M-type Agb Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study of IC 1613, Battinelli & Demers (2009) conclude that a cut at (J − K s ) = 1.40 mag would provide a reliable sample of C-type stars. From Fig.…”
Section: Colour Selection 331 C-and M-type Agb Starsmentioning
confidence: 99%
“…M-type sources were then selected between 0.75 ≤ (J − K) 0 < 1.15 mag and C-type sources were selected at (J − K) 0 ≥ 1.15 mag. A red (J − K) limit was not applied for the selection of the C-type candidates as these sources have been shown to extend to least (J − K) 0 ∼ 2.4 mag (Battinelli & Demers 2009) in IC 1613, and the relatively few sources in our C-type sample with colours redder than this may still be genuine AGB stars that are heavily enshrouded by dust (Zijlstra et al 2006). …”
Section: Blue Limit To M-type Giantsmentioning
confidence: 99%
“…Different techniques adopted for searching C stars lead to samples with different biases (see Battinelli & Demers 2009). The reddest stars are too faint in the optical spectral range to be detected with objective grating techniques, while the four‐filter technique misses the bluest stars (Demers & Battinelli 2002).…”
Section: Colour–magnitude Diagramsmentioning
confidence: 99%
“…The color separations of the C stars from the M-giant stars were determined at (H − K s ) > 0.45 and (J − K s ) > 1.28, where the histogram of M-giant stars drops significantly. The applied color limit in (J − K s ) of the C stars is somewhat bluer than the color limit of (J − K) 0 = 1.4 used in several previous studies (Davidge 2005;Kang et al 2006;Battinelli et al 2007b;Battinelli & Demers 2009). We note that spectroscopic data are necessary for a more accurate identification of M-giant and C stars.…”
Section: Color−color Diagrams and The Selection Of The C Stars Of Ic mentioning
confidence: 61%
“…We note that spectroscopic data are necessary for a more accurate identification of M-giant and C stars. However, Battinelli & Demers (2009) discussed that many C stars probably have a bluer color than the (J − K) 0 = 1.4 limit, and Kacharov et al (2012) indeed found in their spectroscopic data of NGC 6822 that several of the C stars in NGC 6822 have a bluer color than this limit. Thus, our color limit for the C stars is reasonable compared with the other conditions.…”
Section: Color−color Diagrams and The Selection Of The C Stars Of Ic mentioning
confidence: 93%